مسألة الرشد عند العز بن عبد السلام، التي اختلف فيها مع الإمام الشافعي من خلال كتابه قواعد الأحكام في إصلاح الأنام- دراسة مقارنة: Maturity Issue of al-Izz Ibn Abd Salam, Which He Did Not Follow the Imam Shafi’i Through the Book "Rules of judgments": A Comparative Study - Mohamed Mahgoub Ibrahim, Hesham Atta; Ali, Abdul Karim (Online Journal of Research in Islamic Studies, 2019)
The issue of majority (maturity) is one of the important issues in Islamic jurisprudence as it entails terminating control over a minor person (revoking interdiction) and bestowing him control over his properties and actions or measures. Therefore, the jurists have explained the provision of majority in multiple sections of Islamic jurisprudence. And the reason for such disagreement is that al-Izz considered the actions and measures of the young boy good and sound after puberty even if he does not practice his religion well; a view which was rebutted by al-Shafi’i. The aim of this study is to find out both imams’ reasoning for the disagreement and to solve the problem mentioned by al-Izz Ibn Abd Al-Salam related to the condition of al-Shafi’i called ‘practicing religion well’, “That the majority of people do not practice their religion well was ambiguous according to al-Shafi’i”. In this article, the researcher followed the descriptive approach and the inductive method because the researcher induces the views of al-Izz Ibn Abd Al-Salam about the provisions concerning majority, which proves his option. The imam proved his opinion by the linguistic development of words, and with the consensus of Muslims in a rational way. He disagreed with al-Shafi’i on the interpretation of a fundamental rule, which is the interpretation of the word of indefiniteness in the context, as he views it in absolute whereas Shafi’i interprets it in general. Therefore, they had different judgements.